EVALUASI PARAMETER LINGKUNGAN DALAM PELAKSANAAN KEGIATAN PENGASPALAN DI WILAYAH SAMARINDA - Miswara Al-Wadji; Mochamad Gaharu Dida Devedo1; Ardhan Ismail (PROSIDING SEMINAR KIMIA, 2025)
Construction activities have the potential to affect environmental quality, particularly ambient air, noise, vibration, and surface water around project sites. This study aims to analyze the environmental quality of construction activities based on laboratory test results and compare them with the environmental quality standards stipulated in Government Regulation No. 22 of 2021. The research used a descriptive quantitative approach through the analysis of air parameters (NO₂, TSP, CO), noise level, vibration, and river water quality (DO). The laboratory results showed that all parameters were below the environmental quality limits, with NO₂ = 34 µg/Nm³, TSP = 76 µg/Nm³, CO = 206 ppm, noise = 64 dB(A), vibration = 0.2 mm/s, and DO = 6.31 mg/L. These findings indicate that the construction activities did not significantly impact the surrounding environmental conditions. Effective environmental management, controlled heavy equipment operations, and compliance with environmental regulations were key factors in maintaining environmental quality. Therefore, it can be concluded that the monitored construction project met the required environmental standards and remained within safe environmental conditions. Keywords: ambient air, construction wastewater, environmental quality, noise, vibration